Instructor's manual to accompany Probability with statistical applications : - Mosteller, Frederick (Addison-Wesley, 1970)
The theory of probability - the mathematics of uncertainty. Some applications of probability to statistical theory. An understanding of the equivalent of high school Algebra II is required for effective learning from this text.